2021
DOI: 10.1037/xge0000994
|View full text |Cite
|
Sign up to set email alerts
|

Object-based attention prioritizes working memory contents at a theta rhythm.

Abstract: Attention selects relevant information regardless of whether it is physically present or internally stored in working memory. Perceptual research has shown that attentional selection of external information is better conceived as rhythmic prioritization than as stable allocation. Here we tested this principle using information processing of internal representations held in working memory. Participants memorized 4 spatial positions that formed the end points of 2 objects. One of the positions was cued for a del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
5
26
1
Order By: Relevance
“…Spectral analysis (e.g., using Fast-Fourier Transform) of time-course of the accuracy data, obtained via a dense temporal sampling paradigm, revealed that attention fluctuated at theta frequency between the two gratings. Several other studies have replicated this finding (e.g., Fiebelkorn et al, 2013 ; Dugué et al, 2016 ; Senoussi et al, 2019 ; Michel et al, 2021 ; see Kienitz et al, 2021 for a review), and additionally expanded the study of oscillations in behavioral performance to the field of working memory ( Peters et al, 2020 ; Pomper and Ansorge, 2021 ). Of importance, although the findings on fluctuations in attentional sampling might be interpreted as reflecting a different role of oscillations than the one that is proposed in this article, we believe that these potential roles share a core function supported by oscillations, namely to avoid interference.…”
Section: Discussionmentioning
confidence: 79%
“…Spectral analysis (e.g., using Fast-Fourier Transform) of time-course of the accuracy data, obtained via a dense temporal sampling paradigm, revealed that attention fluctuated at theta frequency between the two gratings. Several other studies have replicated this finding (e.g., Fiebelkorn et al, 2013 ; Dugué et al, 2016 ; Senoussi et al, 2019 ; Michel et al, 2021 ; see Kienitz et al, 2021 for a review), and additionally expanded the study of oscillations in behavioral performance to the field of working memory ( Peters et al, 2020 ; Pomper and Ansorge, 2021 ). Of importance, although the findings on fluctuations in attentional sampling might be interpreted as reflecting a different role of oscillations than the one that is proposed in this article, we believe that these potential roles share a core function supported by oscillations, namely to avoid interference.…”
Section: Discussionmentioning
confidence: 79%
“…Here, we focus on perception and attention as cognitive functions of interest, and on the visual sensory modality, which evolved as the predominant sense in primates and provides a rich basis to investigate higher cognitive processes (Scott & Mishkin, 2016;Senoussi & Dugué, 2020;Sereno et al, 1994). Note that most of the reports on behavioural sampling rhythms are for perception and attention, and a lot less for other cognitive functions, such as memory (e.g., Balestrieri et al, 2021;Peters et al, 2020) and decision-making (e.g., Kayser, 2019). Additionally, although such rhythmic behaviour has been also observed in other sensory modalities, and in non-primate species, characterizing rhythms in these other dimensions is beyond the scope of the present review.…”
Section: Behavioural Rhythmsmentioning
confidence: 99%
“…Several other studies have replicated this finding (e.g. (Dugué et al, 2016;Fiebelkorn et al, 2013;Michel et al, 2021;Senoussi et al, 2019), and additionally expanded the study of oscillations in behavioral performance to the field of working memory (Peters et al, 2020;Pomper & Ansorge, 2021). This rapidly growing body of literature provides converging evidence that oscillatory processes are central to behavioral performance in a wide range of cognitive functions, in which they provide both a mechanism to sample or bind information, as well as a capacity limits of these functions.…”
Section: Discussionmentioning
confidence: 73%